Efeito da presença dos taninos nas rações para peixes de águas quentes - Quintero Pinto, Luis Gabriel [UNESP] (2000)
This experiment was undertaken to evaluate the effect of tannin on growth performance and carcass composition of piauçu, for sixty days. Twenty one aquaria (80 L) were supplied with dechlorinated tap-water (1 L/min) in a closed system. Water quality was controled by biologic filter and heater. Fish, with inicial average weight 5.06 g, in a triplicate aquaria were randomly assigned to each of 7 treatments. Experimental diets were formulated to contain approximately 3,200 kcal of digestible energy, 30% crude protein and 0.0, 0.23, 0.46, 0.69, 0.92, 1.37 and 1.82% of total tannin. Although 0.69% of tannin added did not affected apparent feed conversion and protein efficiency ratio, equal or higher levels of 0.46% resulted lower weight gain. Piauçu showed sensitive to condensed tannin wich had significant harmful effect on metabolism and nutrient biologic value of diets nutrients